Cellular target of isoquercetin from Passiflora ligularis Juss for glucose uptake in rat soleus muscle. (1st October 2020) - Rey, Diana; Fernandes, Thaís Alves; Sulis, Paola Miranda; Gonçalves, Renata; Sepúlveda R, Michelle; Silva Frederico, Marisa Jádna; Aragon, Marcela; Ospina, Luís Fernando; Costa, Geison M.; Silva, Fátima Regina Mena Barreto
Abstract: Quercetin 3-O-beta-d -glucopyranoside (isoquercetin) is one of the most frequent metabolites of the Passiflora ligularis Juss. The purpose of this study was to investigate the effect of the aqueous extract and ethanol fraction from P. ligularis Juss leaves on glycaemia and the mechanism of action of isoquercetin on glucose uptake. In the glucose tolerance test, the aqueous extract and ethanol fraction from P. ligularis Juss (125 mg/kg to 500 mg/kg o. g.) reduced glycaemia and increased the hepatic and muscular glycogen content. Phytochemical analysis evidenced the dominant presence of isoquercetin in the extract and fraction from leaves of P. ligularis Juss . Isoquercetin mediates the stimulatory effect on glucose uptake independent of insulin receptor activation but, involve PI3K, MAPK, MEK/ERK pathways and de novo protein synthesis to GLUT-4 translocation. Overall findings revealed that isoquercetin and aqueous extract and ethanol fraction of P. ligularis Juss leaves might be a promising functional food or medicine for the treatment or prevention of diabetes. Graphical abstract: Image 1 Highlights: Passiflora ligularis Juss improves glucose tolerance. Passiflora ligularis Juss increases hepatic and muscular glycogen content. Isoquercetin stimulates glucose uptake independently of insulin receptor activation. Isoquercetin activates PI3K, MAPK, MEK/ERK for glucose uptake. Isoquercetin induces GLUT-4 translocation in skeletal muscle.